Safety and authenticity practices in heritage food production in home-based and commercial catering: a multiple country case study - Almansouri, Mohammad; Verkerk, Ruud; Ab Karim, Shahrim; Abdul Raji, Mohd Nazri; Ismail, Nurul; Nugrahedi, Probo Y.; Luning, Pieternel A. (Elsevier, 2025)
In Saudi Arabia, cooking heritage food dishes has gained popularity owing to increasing attention to the tourism sector. Therefore, food service establishments, such as commercial catering, cook heritage dishes for tourists. In contrast, home-based catering focuses on cooking these dishes for locals. The present study gained insights into the authenticity and safety practices in preparing heritage foods in home-based and commercial catering settings in Saudi Arabia and compared them with those in Indonesia and Malaysia, which have a longstanding history of heritage foods in the hospitality industry. Sixty culinary professionals participated in the study: 30 from home-based catering (10 from each country) and 30 from commercial catering (10 from each country). Semi-structured interviews were used. For authenticity practices, similar findings were observed among all countries, and both catering types checked the availability of essential ingredients in advance as well as taste, flavour and texture to ensure the quality of the recipe. In terms of differences, compared with the culinary professionals in Indonesia and Malaysia, those in Saudi Arabia emphasised the importance of authenticity practices, including having an experienced cook, following specific written recipes, supervising new cooks, providing advice to use the original recipe and presenting authentic dishes without modifications. In terms of similarities in food safety practices, most culinary professionals in the three countries suggested the importance of checking colour and freshness; cleaning equipment with water and chemicals (soap); and wearing protective cooking uniforms (aprons). However, most Saudi Arabian culinary professionals mentioned various other food safety practices compared with other countries, including checking smell, washing hands and regularly changing gloves, washing cooking equipment with special chemicals, closing catering services when owners are unwell or not allowing cooks to work when unwell. These practices can help prevent cross-contamination and produce safe heritage dishes.